MEDIASI DALAM PENYELESAIAN SENGKETA TANAH ULAYAT OLEH NINIK-MAMAK DESA PULAU JAMBU KECAMATAN KUOK KABUPATEN KAMPAR PROVINSI RIAU - Annisa Sundari Ningsih; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The number of tanah ulayat disputes in Kampar Regency specially in the Pulau Jambu village. Sub-district Kuok has brought negative impact to the community. Settlement efforts under taken by Ninik-Mamak as tribal elders in governing customary land has been through mediation with the parties, with the involvement of other tribal Ninik-Mamak, empat jini (Tuo Kampuong, Dubalang, Malin and scholars), the Village Head, religious leaders and children's nephew. In the mediation course there are communication processes, techniques and strategies given by a mediator (ninik-Mamak) in order to achieve mediation. This study aims to determine how the mediation process conducted by Ninik-Mamak in dispute resolution tanah ulayat in the District of Kampar sub-district Kuok and investigate the factors that influence the process of dispute resolution mediation tanah ulayat by ninik-Mamak.This study uses qualitative descriptive approach, the data collected with observation, interview and documentation. The data have been acquired and processed to be reduced and presented in order to obtain a general conclusion. This research was conducted in the Pulau Jambu village, district Kampar, Sub-district Kuok. With the object of research is mediation in the settlement of tanah ulayat disputes by ninik-Mamak in the Pulau Jambu village, district Kampar, Sub-district Kuok. Subjects in this study amounted to10 people based on purposive method. As for the validity of the data examine researchers using participatory extension techniques and triangulation.The results showed that the mediation process conducted by Ninik-Mamak using the facilitation model. Before the mediation process, Ninik-Mamak in resolving disputes of tanah ulayat begins with the steps that must be done that is a complaint, the calling party to the dispute, calling witnesses, reviewing or identifying interests. While the mediation process is the opening by a mediator, finding common ground, identify options of the parties, the determination of which option is selected, and the deal. In addition, factors that used effects the mediation process there are two other factors that influence the success of mediation is the motivation and competence of mediators while the factors that influence the success of mediation is not a lack of understanding of customary law, lack of government support and the absence of a witness history.Keyword: Communication, Mediationt, Resolve Disputes and Tanah Ulayat